2020
DOI: 10.3390/biom10030423
|View full text |Cite
|
Sign up to set email alerts
|

Fish-Derived Antifreeze Proteins and Antifreeze Glycoprotein Exhibit a Different Ice-Binding Property with Increasing Concentration

Abstract: The concentration of a protein is highly related to its biochemical properties, and is a key determinant for its biotechnological applications. Antifreeze proteins (AFPs) and antifreeze glycoproteins (AFGPs) are structurally diverse macromolecules that are capable of binding to embryonic ice crystals below 0 °C, making them useful as protectants of ice-block formation. In this study, we examined the maximal solubility of native AFP I–III and AFGP with distilled water, and evaluated concentration dependence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Similar observations have been reported for hyperactive AFPs, including Tis AFP8 22 , Col AFP 20 Mp AFP_RIV 31 , sbwAFP ( C. fumiferana ) 37 , and Tm AFP ( Tenebrio molitor ) 37 . Some moderately active AFPs, when assayed at a relatively high concentration (0.1 mg/ml), also exhibit whole-hemisphere binding, e.g., BpAFP 14 and AFPII 38 ( Brachyopsis rostratus ), with a concentration-dependent multiple-plane binding. In the current study, FIPA analysis of Tis AFP7 was performed using a low protein concentration (0.007 mg/ml); the protein’s multiple-plane binding ability was higher than those of the typical moderately active AFPs.…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations have been reported for hyperactive AFPs, including Tis AFP8 22 , Col AFP 20 Mp AFP_RIV 31 , sbwAFP ( C. fumiferana ) 37 , and Tm AFP ( Tenebrio molitor ) 37 . Some moderately active AFPs, when assayed at a relatively high concentration (0.1 mg/ml), also exhibit whole-hemisphere binding, e.g., BpAFP 14 and AFPII 38 ( Brachyopsis rostratus ), with a concentration-dependent multiple-plane binding. In the current study, FIPA analysis of Tis AFP7 was performed using a low protein concentration (0.007 mg/ml); the protein’s multiple-plane binding ability was higher than those of the typical moderately active AFPs.…”
Section: Resultsmentioning
confidence: 99%
“…AFPs can prevent the growth of ice crystals and can decrease the freezing point of the solution. Because of their THA, AFPs are the most important factor in the antifreeze process of cells and organisms (Inagawa et al, 2020; Tsuda et al, 2020; Ye et al, 2020). We identified one AFP with a THA of 0.97°C in a previous study (Yu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This observation was interpreted as indicating that this IBP binds only to the pyramidal plane at 0.01 mg/mL, whereas it covers the whole ice crystal, including the basal plane, when its concentration is 10 times higher [40]. A similar change was observed for type II IBP from longsnout poacher (LpIBP) [41]. We performed a concentration dependence experiment for AnpIBP between 0.01 and 0.15 mg/mL.…”
Section: Fipa Of Anpibp Showed a Novel Prism-ring Patternmentioning
confidence: 64%
“…It has been shown that the FIPA pattern is sometimes changed with increases in the concentration of IBP [40,41]. For example, the pattern was observed in a limited area for a 0.01-mg/mL solution of fish type I IBP from barfin plaice, and it was overcast by the entire illumination when the protein concentration was increased to 0.1 mg/mL.…”
Section: Fipa Of Anpibp Showed a Novel Prism-ring Patternmentioning
confidence: 99%